Cell autonomous TLR4 signaling modulates TGF-β induced activation of human cardiac fibroblasts - Gayathri Vijayakumar; Anisha Latha; Aiswaria P. Anil; Yogini Surve; Aiswarya R; Bipin G. Nair; Indulekha CL. Pillai (Heliyon)
Fibrosis is one of the major outcomes following injury in the heart. Immune response in the injury niche modulates fibrosis, yet little is known about how cell-autonomous immune signaling in adult cardiac fibroblasts regulates fibrosis. Using FACS, single-cell sequencing of cardiac fibroblasts from Collagen1-α1GFP mice and human heart failure patients, we demonstrate that TLR4 is the major immune sensor expressed in cardiac fibroblasts. Inhibition of TLR4 signaling reduces TGF-β induced fibrotic changes such as contractibility and migration of adult human cardiac fibroblasts in TGF-β treated fibrotic conditions. TGF-β treated cardiac fibroblastss show enhanced cytokine expression, and inhibition of TLR4 signaling reduces the expression of cytokines, thereby reducing TGF-β targets such as extracellular matrix genes. Thus, our data demonstrate that TLR4 and other signaling molecules downstream of TLR4 are expressed in cardiac fibroblast, and inhibition of TLR4 modulates fibrotic changes in vitro.